High-frequency trading data forecasting model using quantum-based approach - Ishak, Iskandar; Ahmad Zukarnain, Zuriati; Sidi, Fatimah; Ibrahim, Hamidah; Palaniappan, Visalakshi (Kyushu Institute of Technology, 2024)
This research attempts to enhance SVM model optimization through Quantum computing. Quantum approach performs calculations based on qubits, where the probability of an object's state, instead of just 1s or 0s rather applied on superposition. This gives the potential to process exponentially more data compared to classical computers [2]. Datasets used are SP500 HFT dataset and Apple Inc. (AAPL) stocks from 2017 to 2018.